Semi-Average Sampling for Shift-Invariant Signals in a Mixed Lebesgue Space. (3rd July 2020) - Jiang, Yingchun; Kou, Junke
Abstract: This article mainly studies the nonuniform and semi-average sampling of time-varying shift-invariant signals living in a mixed Lebesgue space L p, q ( R d + 1 ), under the condition that the generator φ of the shift-invariant subspace belongs to a hybrid-norm space of mixed form depending on the orders p and q . First, the sampling stability for two kinds of semi-average sampling functionals is established. Then, we give the corresponding iterative approximation projection algorithms with exponential convergence for recovering the time-based shift-invariant signals from the semi-average samples.